FEATURES OF ENDOTHELIAL DYSFUNCTION AND VEGETATION OF DYSTONIA AT DUODENAL ULCER FOR STUDENTS - Oparin, А.; Dvoyaschkina, J.; Khomenko, L. (World of Medicine and Biology, 2013)
It is shown that in patients with Hp-associated duodenal ulcer with vegetovascular disorders in exacerbation period appears endothelial dysfunction, intensity and character of it depends on the hypotonic or hypertonic type of NCD. The data prove that the endothelial dysfunction, first provoked by Hp endothelial influence, can become not only the factor of microcirculation disturbances but one of the reasons of NCD appearance in patients with duodenal ulcer.
Keywords: duodenal ulcer; endotelin-1; nitric oxide; vegetation dysfunction